A step forward in the genome characterization of the sugarcane borer, Diatraea saccharalis: karyotype analysis, sex chromosome system and repetitive DNAs through a cytogenomic approach - Gasparotto, Ana E. [UNESP]; Milani, Diogo [UNESP]; Martí, Emiliano [UNESP]; Ferretti, Ana Beatriz S. M. [UNESP]; Bardella, Vanessa B. [UNESP]; Hickmann, Frederico; Zrzavá, Magda; Marec, František; Cabral-de-Mello, Diogo C. [UNESP] (Springer Nature, 2022)
Moths of the family Crambidae include a number of pests that cause economic losses to agricultural crops. Despite their economic importance, little is known about their genome architecture and chromosome evolution. Here, we characterized the chromosomes and repetitive DNA of the sugarcane borer Diatraea saccharalis using a combination of low-pass genome sequencing, bioinformatics, and cytogenetic methods, focusing on the sex chromosomes. Diploid chromosome numbers differed between the sexes, i.e., 2n = 33 in females and 2n = 34 in males. This difference was caused by the occurrence of a WZ1Z2 trivalent in female meiosis, indicating a multiple sex-chromosome system WZ1Z2/Z1Z1Z2Z2. A strong interstitial telomeric signal was observed on the W chromosome, indicating a fusion of the ancestral W chromosome with an autosome. Among repetitive DNAs, transposable elements (TEs) accounted for 39.18% (males) to 41.35% (females), while satDNAs accounted for only 0.214% (males) and 0.215% (females) of the genome. FISH mapping revealed different chromosomal organization of satDNAs, such as single localized clusters, spread repeats, and non-clustered repeats. Two TEs mapped by FISH were scattered. Although we found a slight enrichment of some satDNAs in the female genome, they were not differentially enriched on the W chromosome. However, we found enriched FISH signals for TEs on the W chromosome, suggesting their involvement in W chromosome degeneration and differentiation. These data shed light on karyotype and repetitive DNA dynamics due to multiple chromosome fusions in D. saccharalis, contribute to the understanding of genome structure in Lepidoptera and are important for future genomic studies.
Keywords: Chromosome fusion; FISH; Holocentric chromosome; Multiple sex chromosomes; satDNA; W chromatin